Endoscopic Ultrasound-Guided Drainage of Intra-Abdominal Abscess after Gastric Perforation in a Patient Receiving Ramucirumab and Paclitaxel for Advanced Gastric Cancer - Koichiro Mandai (Case Reports in Oncology, 2017)
Gastrointestinal perforation is a serious adverse event that occurs in approximately 1% of patients receiving ramucirumab and paclitaxel. A 67-year-old man with unresectable advanced gastric cancer was admitted to our hospital and treated with ramucirumab and paclitaxel. Gastric perforation occurred during the second cycle of chemotherapy. Although the patient’s condition improved without surgery, an abscess developed in the intra-abdominal fluid collection resulting from the perforation. We performed endoscopic ultrasound-guided abscess drainage. The patient improved and was discharged in satisfactory condition. Endoscopic ultrasound-guided drainage is a treatment option for patients with intra-abdominal abscess following gastric perforation due to ramucirumab.